POLITICAL ECONOMY OF CROSS-BORDER TRADE BETWEEN INDONESIA AND MALAYSIA: LOCAL PRODUCT OPPORTUNITIES AND CHALLENGES IN WEST KALIMANTAN - Darmastuti, Shanti; Nidatya, Nurfarah; Saraswati, Dini Putri; Rahmalia, Alfiyah Nur; Radjasa, Andhika Fathir (Universitas Padjadjaran, 2026)
As a key element of the political economy, cross-border trade makes a substantial contribution to community welfare while also supporting national economic growth. West Kalimantan, which borders Sarawak, Malaysia, serves as a strategic economic corridor in Indonesia, facilitating the movement of people and goods through the National Border Post. Although local products are the main commodities traded at this border, issues of product competitiveness, market stability, and border security pose major challenges to trade. Within the framework of cross-border political economy, this study examines both the opportunities and challenges in trading local products. It emphasizes how government initiatives, institutional coordination, and security management shape sustainable trade. Data was collected using a qualitative approach through in-depth interviews with institutional representatives, the Indonesian Consulate General in Kuching, central and local government officials, and document analysis. Triangulation of methods and sources was used to ensure data validity. The study shows that good political coordination, institutional synergy, and border stability are essential to improving the competitiveness of local products in cross-border trade.